Challenging local government notions of community engagement as unnecessary, unwanted and unproductive: Case studies from rural Australia - McKenzie, Fiona Haslam; Pini, Barbara (Routledge, 2006)
Despite the fact that sustainability is typically viewed as being dependent upon community engagement at the local level, this paper reveals that there has been a limited emphasis on community involvement in environmental management in rural local government areas in Australia. Using interviews with 67 council staff and elected members from 15 rural government case study sites across four states in Australia, the paper documents the ways in which a lack of emphasis on community participation is legitimized and rationalized by rural local governments. Three key arguments are made by participants. The first is that community engagement is irrelevant in rural areas as the small population means that people have ready daily access to their councillors and that, in turn, councillors have an intimate knowledge of their constituents' interests and concerns. The second is that community engagement for sustainability is unwanted by rural residents who prioritize economic development concerns above the environment. The third rationale given by research participants to justify limited community engagement is that the practice is unproductive. The contention made is that involving community is time-consuming, costly and typically produces little relevant tangible outcomes. The paper concludes by countering these arguments, while acknowledging that rural local governments do face particular financial and human resource limitations in relation to community engagement.